2015
DOI: 10.1097/j.pain.0000000000000214
|View full text |Cite
|
Sign up to set email alerts
|

Towards a new model of attentional biases in the development, maintenance, and management of pain

Abstract: Individuals with chronic pain demonstrate attentional biases (ABs) towards pain-related stimuli. However, the clinical importance of these biases is yet to be determined and a sound theoretical model for explaining the role of ABs in the development and maintenance of pain is lacking. Within this article, we (1) systematically review prospective and experimental research exploring ABs and pain outcomes in light of current theoretical models and (2) propose a theoretical framework for understanding AB in pain. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
197
5
4

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 124 publications
(220 citation statements)
references
References 41 publications
14
197
5
4
Order By: Relevance
“…Indeed, research on AB to pain has mainly focused on its role in healthy participants and experimental pain tasks (e.g., the coldpressor paradigm [42,49]). In this way, the current findings corroborate demonstrated associations between AB to pain and reported pain and disability among individuals with chronic pain [4, 33,48].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, research on AB to pain has mainly focused on its role in healthy participants and experimental pain tasks (e.g., the coldpressor paradigm [42,49]). In this way, the current findings corroborate demonstrated associations between AB to pain and reported pain and disability among individuals with chronic pain [4, 33,48].…”
Section: Discussionmentioning
confidence: 99%
“…They did not however find any relationship between attentional biases and pain outcomes. Conversely, we recently reviewed prospective studies and found that avoidance of salient stimuli or a bias towards positive stimuli predicted chronicity (Todd et al, 2015).…”
Section: Introductionmentioning
confidence: 98%
“…Research exploring the role of attentional biases in the experience of pain is growing rapidly, with a number of recent systematic reviews (Pincus & Morley, 2001;Todd et al, 2015) and metaanalyses (Crombez, Van Ryckeghem, Eccleston, & Van Damme, 2013;Schoth, Nunes, & Liossi, 2012) having been published. Importantly, although most researchers agree that attentional biases play a role in pain, the specific nature of these attentional biases is still yet to be determined and research to date remains somewhat inconsistent regarding the best parameters under which to detect these biases.…”
Section: Introductionmentioning
confidence: 99%
“…Definitely, there is room for improvement, but space limitations do not allow us to elaborate this further. Following the rationale on the causal role of attentional bias in anxiety and fear (Hakamata et al, 2010), pain researchers have formulated a similar role for attentional bias in the development and maintenance of chronic pain (Todd et al, 2015). They also argued to directly modify the attentional bias towards painrelated information by teaching patients to direct their attention away from pain-related information (Sharpe et al, 2012).…”
Section: Pain and Attentional Biasmentioning
confidence: 99%